2012
DOI: 10.1007/s00248-012-0008-z
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Seawater Bacteria Harbor a Large Reservoir of Plasmid-Mediated Quinolone Resistance Determinants in Jiaozhou Bay, China

Abstract: Diversity and prevalence of plasmid-mediated quinolone resistance determinants were investigated in environmental bacteria isolated from surface seawater of Jiaozhou Bay, China. Five qnr gene alleles were identified in 34 isolates by PCR amplification, including qnrA3 gene in a Shewanella algae isolate, qnrB9 gene in a Citrobacter freundii isolate, qnrD gene in 22 Proteus vulgaris isolates, qnrS1 gene in 1 Enterobacter sp. and 4 Klebsiella spp. isolates, and qnrS2 gene in 1 Pseudomonas sp. and 4 Pseudoalteromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 78 publications
(104 reference statements)
1
20
0
1
Order By: Relevance
“…Qnr-encoding genes have already been reported in such an environment [16]. The current results point to the role of coastal waters as reservoirs and vectors of MDR micro-organisms in cities with insufficient sewage treatment infrastructure, with potential to accelerate the spread of resistance in the community.…”
Section: Discussionmentioning
confidence: 81%
“…Qnr-encoding genes have already been reported in such an environment [16]. The current results point to the role of coastal waters as reservoirs and vectors of MDR micro-organisms in cities with insufficient sewage treatment infrastructure, with potential to accelerate the spread of resistance in the community.…”
Section: Discussionmentioning
confidence: 81%
“…Because nitrofurantoin and sulfadimethoxine are synthetic antibiotics, microbes would not experience these molecules in natural microbe-microbe interactions. Resistant bacteria have been isolated from marine environments in proximity to aquaculture facilities or waterways in proximity to human influence (23,(25)(26)(27). In addition, Port and colleagues (24) showed that frequencies of known antibiotic resistance genes were higher nearshore, so anthropogenic inputs can influence resistance patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Conjugation experiments were performed by the broth mating assay as previously described, with some modifications [15]. Prior to the conjugation experiments, the donor and recipient strains were tested respectively for susceptibility to sodium azide (200 mg/ L) and ceftazidime (1 mg/L).…”
Section: Conjugation Experimentsmentioning
confidence: 99%